Transition Of The Garo Matrilineal Society In Garo Hills Region Of Meghalaya-A Study (Journal of Namibian Studies : History Politics Culture, 2023)
The Meghalaya Society of Matrilineal culture can be seen and discovered  among the Garos, Khasi, and Jaintia tribes of Northeast India. The Garo, Khasi,  and Jaintia trace their ancestry back to their mother. The mother’s totem or clan is passed down to her descendants. The title of identification is also from the mother’s side. In terms of property, the daughter inherits. Women do not reign or dominate in Garo Society, nor do they have more power than men. Garo women have more independence than women in patriarchal societies. In Garo society, both men and women succeed in all spheres of social and religious activity. Women in Garo society inherit property.